High-resolution XRF (Itrax) elemental composition of sediment core YMER80-131 - George Kontsevich; Ludvig Löwemark (PANGAEA, 2021)
Core Number: 131, Core Type: Super Gravity Corer (SGC), Sediment Depth: 349cm, Water Depth: 820m, Latitude: 81° 07 extquotesingle Longitude: 03° 12 extquotesingle, Core was taken in September 5th 1980. This is re-evaluated data of 080604\YMER80\YMER80_MG-131_0-64cm_A_Mo\XRF data from 2008-06-18. Core was scanned using the ITRAX XRF core scanner and cores were merged using Corascope.